2008
DOI: 10.1016/j.ssi.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic glass transition and fragility of lithium borate binary glass

Abstract: The compositional variations of the fragility of lithium borate binary glasses have been investigated over a wide composition range up to 64 mol% of Li 2 O. The frequency dependences of the dynamic heat capacity C p (ω) above the dynamic glass transition temperature T g have been observed by Temperature-Modulated DSC. The fragility or steepness index m has been determined. The composition dependence has been discussed on the basis of the fragility model proposed by Vilgis, and it has been revealed that the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…However, the formation of four‐coordinated boron in lithium borate glasses could enhance the connectivity inside the three‐dimensional network . There is strong correlation between the glass fragility and the fluctuation of the coordination number of boron . The glass density and four‐coordinated boron fraction are also strongly correlated …”
Section: Introductionmentioning
confidence: 99%
“…However, the formation of four‐coordinated boron in lithium borate glasses could enhance the connectivity inside the three‐dimensional network . There is strong correlation between the glass fragility and the fluctuation of the coordination number of boron . The glass density and four‐coordinated boron fraction are also strongly correlated …”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the physical properties such as sound velocity, 9) stretched exponentiality KWW 10) and fragility 11) show the strong composition dependences.…”
mentioning
confidence: 96%
“…TM‐DSC has previously been used to determine the fragility of both chalcogenide and oxide glass‐forming systems . However, due to instrumental limitations, this has been limited to glasses with low T g (below ~550°C), and it has thus not been suitable for many high‐ T g silicate glasses of industrial importance.…”
Section: Theorymentioning
confidence: 99%
“…Instead, a technique for measuring the structural relaxation time of glasses based on specific heat capacity spectroscopy measurements was proposed in 1985, using the thermal relaxation caused by the isothermal temperature oscillations to measure the structural relaxation time. Using the frequency dependence of the peak temperature (Tgω) in the imaginary heat capacity, TM‐DSC has successfully been applied to determine m of several borate‐based glass‐forming liquids ( T g ≈ 450°C) by converting frequency into relaxation time and using the following equation,mfalse(xfalse)=|dlog10τfalse(T,xfalse)d(Tgfalse(xfalse)/T)T=Tgfalse(xfalse).…”
Section: Theorymentioning
confidence: 99%